“KITA PUNYA BENDERA”: CHINESE ETHNIC AND NATIONALISM NARRATIVES - Wibawa, Satrya (Capture : Jurnal Seni Media Rekam, 2018)
This paper discusses Indonesian cinema‟s representation of children after the fall of the New Order and during the Reform era. Thus, I explore Kita Punya Bendera1 (2008) that seemingly stands as the first children‟s film that places a Chinese ethnic background child as the main narrative which also focuses on the complicated situation of being a Chinese in Indonesia. Considering the state‟s overpowering political hegemony during the New Order, the key question with respect to the period of transition concerns that which remains the same amidst the change. The paper argues that, in spite of deep transformations, the cinematic representation of children remains as an ideological model for projecting Indonesia as an improved nation, which is done by featuring ethnic and racial diversitiy as it intersects with a changing idea of children and its significant relation with family culture and the education system in Indonesia.